2011
DOI: 10.1186/cc10064
|View full text |Cite
|
Sign up to set email alerts
|

Quality of interhospital transport of the critically ill: impact of a Mobile Intensive Care Unit with a specialized retrieval team

Abstract: IntroductionIn order to minimize the additional risk of interhospital transport of critically ill patients, we started a mobile intensive care unit (MICU) with a specialized retrieval team, reaching out from our university hospital-based intensive care unit to our adherence region in March 2009. To evaluate the effects of this implementation, we performed a prospective audit comparing adverse events and patient stability during MICU transfers with our previous data on transfers performed by standard ambulance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 12 publications
6
81
0
13
Order By: Relevance
“…In a literature review, Droogh et al (2015) concluded that the number of transfers is likely to increase with the centralization of specialized care. Wiegersma et al (2011) found that specialist consultations or advanced/specialized therapy were the main indications for transfer, which is in line with the results found in this study, where 38% of patients were transferred to be examined by specialist and 37% to perform specialized therapeutic interventions. The SUMC of ULSNE -Hospital Unit of Bragança integrates the second level of care and is located in the north region of the country; hence, patients who cannot be treated there must be transferred.…”
Section: Characterization Of the Clinical Profilesupporting
confidence: 81%
See 1 more Smart Citation
“…In a literature review, Droogh et al (2015) concluded that the number of transfers is likely to increase with the centralization of specialized care. Wiegersma et al (2011) found that specialist consultations or advanced/specialized therapy were the main indications for transfer, which is in line with the results found in this study, where 38% of patients were transferred to be examined by specialist and 37% to perform specialized therapeutic interventions. The SUMC of ULSNE -Hospital Unit of Bragança integrates the second level of care and is located in the north region of the country; hence, patients who cannot be treated there must be transferred.…”
Section: Characterization Of the Clinical Profilesupporting
confidence: 81%
“…The most common diagnosis was neurological disease, followed by cardiovascular disease. In an observational study conducted by Wiegersma et al (2011) in the northeast region of the Netherlands on patient transfers to more differentiated hospitals, the main diagnosis of transfer was respiratory failure (27%), followed by sep-sis (17.6%), and multi-organ failure (10.8%). These results are contrary to those found in this study, where respiratory diseases appear in fifth place.…”
Section: Characterization Of the Clinical Profilementioning
confidence: 99%
“…However, in the study of van Lieshout et al adverse events occurred in 15-16 % of transports in both groups [1]. In another study we found that the percentage of adverse events during transports performed with a dedicated MICU team was 12.5 % [2], and in a successive study most adverse events appeared to be caused by failure of technical equipment [3]. It would appear, therefore, that adverse events can be patient-or equipment-related, or both, and may differ in seriousness.…”
mentioning
confidence: 68%
“…This is because the transfer by a mobile intensive care unit staffed by trained physicians imposes less risk to critically ill patients than a transfer by standard ambulance 4. In addition, the benefits of DH include the highest level of prehospital medical care and transportation 5.…”
Section: Discussionmentioning
confidence: 99%